-3
Пошаговое объяснение:
Приступлю к решению:
Домножу все на (x-1)(x+1):
ОДЗ:
1 не подходит по ОДЗ:
x = -3
(x+2) / (x-1) + (x+3) / (x+1) = (x+5) / (x^{2} -1) | домножаем на (x^{2} -1)
Условие: x ≠ 1; -1
(x+2)(x+1) + (x+3)(x-1) = x+5
x^{2} + 3x + 2 +x^{2} + 2x - 3 = x + 5
2x^{2} + 4x - 6 = 0 | делим на 2
x^{2} + 2х - 3 = 0
D = 4 - 4 * 1 * (-3) = 4 + 12 = 16
ответ: x = -3
-3
Пошаговое объяснение:
Приступлю к решению:
Домножу все на (x-1)(x+1):
ОДЗ:
1 не подходит по ОДЗ:
x = -3
Пошаговое объяснение:
(x+2) / (x-1) + (x+3) / (x+1) = (x+5) / (x^{2} -1) | домножаем на (x^{2} -1)
Условие: x ≠ 1; -1
(x+2)(x+1) + (x+3)(x-1) = x+5
x^{2} + 3x + 2 +x^{2} + 2x - 3 = x + 5
2x^{2} + 4x - 6 = 0 | делим на 2
x^{2} + 2х - 3 = 0
D = 4 - 4 * 1 * (-3) = 4 + 12 = 16
x первый = (-2 + 4) / 2 = 1 Не подходит по условиюx второй = (-2 - 4) / 2 = -3ответ: x = -3